Evaluation of total ozone extremes at Poprad-Gánovce - NOWAKOVÁ, Barbara (Contributions to Geophysics and Geodesy, 2021)
The aim of this paper is the selection of appropriate criteria for extreme total ozone (TO3) events detection, evaluation of frequency and annual distribution of TO3 extremes and comparison of the frequency of extremely low and extremely high TO3 events observed at Poprad-Gánovce (49° 03′N, 20° 32′E, 710 m a.s.l.) during the 1994–2004 period and at the closest TO3 observatory Hradec Králové (50° 18′N, 13° 83′E, 235 m a.s.l.) during the 1962–1990 period. The results of statistical analysis enabled the usage of long-term TO3 average from Hradec Králové as a climatological “normal” for the observatory at Poprad-Gánovce. The occurrence of below- and above-normal TO3 at Poprad-Gánovce was evaluated with respect to both the 1994–2004 Poprad-Gánovce data and the 1962–1990 Hradec Králové data. Three methods were used for the selection of extreme TO3 events. Firstly, daily TO3 was considered to be below-normal (above-normal), when it was below (up to) the 80% (120%) of daily mean value Ō3 calculated by the robust locally weighted regression method. Then, the smoothed daily mean of TO3 Ō3 and its standard deviation σ were used for selection of below- or above-normal TO3 values. The third method coupled both the mentioned methods. The number of cases with below-normal TO3 was nearly the same, if an extreme occurrence was determined by both methods with respect to the Poprad-Gánovce average TO3. As soon as the Hradec Králové 1962–1990 average TO3 values were applied to the extreme total ozone values separation, the number of extremely low TO3 values rapidly increased. The relationship between TO3 extremes and extremes in tropopause and in standard pressure level, characteristics was studied, too.